The “Irresponsibility of the Outsider”? American Expatriates and Italian Fascism - Isabelle Richet (Association Française d'Etudes Américaines, 2014)
The article looks at expatriation as one of the many borderlands where Americans have been brought into contact with other cultures and social realities. In trying to make sense of the relationship expatriates have established with their chosen country, it questions the notion of an “outsider status” often claimed by the self-exiled writers of the 1920s. It looks instead at the contradictory personal and social dynamics that have determined the nature of the expatriates’ engagement with their host society. It focuses on expatriates in Italy during the twenty years of the fascist regime and combines a typological and biographical approach. It analyzes four possible stands toward the dictatorship —active pro-fascist, passive pro-fascist, passive anti-fascist, active anti-fascist—through the experience of four expatriates: George Nelson Page, scion of the famous Virginia planter family; Iris Cutting Origo, raised among the wealthy Anglo-American colony of Florence; the art critique Bernard Berenson and Robert Winston Wiley, a young radical from the Mid-West who contributed articles to the magazine Common Sense. This approach highlights the complex articulation of a number of personal, social and political determinants that fashioned the attitude these expatriates adopted toward the dictatorship. It also indicates that the expatriate experience does not lend itself to sweeping generalizations but needs to be carefully contextualized and historicized.